2015
DOI: 10.1216/jie-2015-27-3-407
|View full text |Cite
|
Sign up to set email alerts
|

Boundary integral solution of potential problems arising in the modelling of electrified oil films

Abstract: We consider a class of potential problems on a periodic half-space for the modelling of electrified oil films, which are used in the development of novel switchable liquid optical devices (diffraction gratings). A boundary integral formulation which reduces the problem to the study of the oil-air interface alone is derived and solved in a highly efficient manner using the Nyström method. The oil films encountered experimentally are typically very thin and thus an interface-only integral representation is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In the examples considered later, a closed form expression will be available for φ H ; however, in general it may be necessary to approximate φ H by, for example, a truncated Fourier series (if solving the half-plane problem via separation of variables) or quadrature (if computing φ H directly from the boundary integral formula (3.3)). It is shown in Chappell (2015) that the integral equation (3.17) has a unique bounded solution for any 1 , 2 > 0. In order to combine the above-described fluid and electric potential models, we note that the fluid equations depend on the normal and tangential derivatives of φ on Γ I (see (3.16)), rather than on φ itself.…”
Section: Green's Functions and The Periodic Half-plane Potentialmentioning
confidence: 99%
See 4 more Smart Citations
“…In the examples considered later, a closed form expression will be available for φ H ; however, in general it may be necessary to approximate φ H by, for example, a truncated Fourier series (if solving the half-plane problem via separation of variables) or quadrature (if computing φ H directly from the boundary integral formula (3.3)). It is shown in Chappell (2015) that the integral equation (3.17) has a unique bounded solution for any 1 , 2 > 0. In order to combine the above-described fluid and electric potential models, we note that the fluid equations depend on the normal and tangential derivatives of φ on Γ I (see (3.16)), rather than on φ itself.…”
Section: Green's Functions and The Periodic Half-plane Potentialmentioning
confidence: 99%
“…In Chappell (2015) it is shown that (3.18) has a unique bounded solution in the Sobolev space H −1/2 (Γ I ) -see for example Kress (1989, § 8.2) for an introduction to Sobolev spaces. The solution procedure is thus to first find the potential φ correponding to the initially flat interface y = h 0 by solving (3.17), and to compute the required normal derivative via (3.18).…”
Section: Green's Functions and The Periodic Half-plane Potentialmentioning
confidence: 99%
See 3 more Smart Citations